Building Structures : Understanding The Basic - Millais,Malcom (Routledge,Taylor & Francis Group, 2017)
This is a one-stop book for knowing everything important about building structures.Self-contained and with no prerequisites needed,it is sutiable for both general readers and building profesionals,follow the history of structural understanding grasp the concepts of structural behaviour via step by step explanations.